2015
DOI: 10.1364/ao.54.002776
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared Mueller ellipsometer with pseudo-achromatic optical elements

Abstract: The purpose of this article is to present a new broadband Mueller ellipsometer designed to work in the midinfrared range, from 3 to 14 microns. The Mueller ellipsometer, which can be mounted in reflection or in transmission configuration, consists of a polarization state generator (PSG), a sample holder, and a polarization state analyzer (PSA). The PSG consists in one linear polarizer and a retarder sequentially rotated to generate a set of four optimal polarization states. The retarder consists in a bi-prism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Indeed, there have recently been several studies that have demonstrated this potential. 11,12,25,28,29 Notably, Hinrichs et al, 11 recently showed the sensitivity of transmission cross-polarized FTIR to rapidly identify the anisotropy of polymer nanofibers. Given the previous discussion regarding the transmittance through crossed polarizers with respect to sample thickness, this approach appears to hold potential for analyzing the anisotropy of samples that are generally too thick for traditional FTIR methods.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there have recently been several studies that have demonstrated this potential. 11,12,25,28,29 Notably, Hinrichs et al, 11 recently showed the sensitivity of transmission cross-polarized FTIR to rapidly identify the anisotropy of polymer nanofibers. Given the previous discussion regarding the transmittance through crossed polarizers with respect to sample thickness, this approach appears to hold potential for analyzing the anisotropy of samples that are generally too thick for traditional FTIR methods.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most p-FTIR studies utilizing polarizer–analyzer configurations are conducted with parallel-oriented polarizers. ,,,, However, the results presented in the previous section illustrate the potential of a cross-polarized FTIR approach for analyzing the anisotropy of organic materials, particularly the birefringent components, as one would expect, which are nearly unnoticeable in the parallel-oriented configurations. Indeed, there have recently been several studies that have demonstrated this potential. ,,,, Notably, Hinrichs et al, recently showed the sensitivity of transmission cross-polarized FTIR to rapidly identify the anisotropy of polymer nanofibers. Given the previous discussion regarding the transmittance through crossed polarizers with respect to sample thickness, this approach appears to hold potential for analyzing the anisotropy of samples that are generally too thick for traditional FTIR methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation